Facilitators of and obstacles to practitioners' adoption of harm reduction in cannabis use: a scoping review - Roula Haddad; Christian Dagenais; Jean-Sébastien Fallu; Christophe Huỳnh; Laurence D'Arcy; Aurélie Hot (BMC, 2024)
Abstract Background Cannabis use can generate potential avoidable harms, hence the need for effective preventive measures and treatment. Studies show the efficacy of harm reduction (HR) in minimizing undesirable consequences associated with this use. Despite its proven efficacy, HR in cannabis use remains poorly applied by many health and social services (HSS) practitioners, especially with young people. However, knowledge regarding the underlying reasons for this is limited. To fill this gap, we aimed to identify facilitators of and obstacles to HSS practitioners' adoption of HR in cannabis use across OECD countries. Methods We conducted a scoping review, guided by Arksey and O'Malley's model. The search strategy, executed on health databases and in the grey literature, captured 1804 studies, of which 35 were retained. Data from these studies were extracted in summary sheets for qualitative and numerical analysis. Results Facilitators and obstacles were grouped into four themes: stakeholders' characteristics (e.g., education, practice experience); clients' characteristics (e.g., personal, medical); factors related to HR (e.g., perceived efficacy, misconceptions); factors related to the workplace (e.g., type of workplace). Data were also extracted to describe the populations recruited in the selected studies: type of population, clientele, workplace. Conclusion Several factors might facilitate or hinder HSS practitioners' adoption of HR in cannabis use. Taking these into consideration when translating knowledge about HR can improve its acceptability and applicability. Future research and action should focus on this when addressing practitioners' adoption of HR.